COMBINING ENTERPRENEURIAL AND SPIRITUAL LEADERSHIP FOR MANAGING PUBLIC EDUCATIONAL ORGANIZATION: A CONCEPTUAL THINKING - Iriyanto Iriyanto (UIN Sunan Kalijaga, 2016)
The society demands in the field of education continue to increase over time. Therefore, public education institutions must constantly adapt to the society needs and demands. To realize effective public education institutions will require a creative leader in the organizational management. One strategy that can be taken by a leader is to combine the values of entrepreneurship and Islamic spirituality in managing the public educational organization. The analysis showed that this leadership model is can improving organizational performance without having to leave the obligations as a Muslim. Spirituality Islam became a trigger awareness to improve performance within the organization. Keywords: Leadership, Entrepreneurial, Spiritual, Organizational Management